2017
DOI: 10.1212/wnl.0000000000004241
|View full text |Cite
|
Sign up to set email alerts
|

Journal Club: Long-term functional outcome in patients with acquired infections after acute spinal cord injury

Abstract: Journal Club: Long-term functional outcome in patients with acquired infections after acute spinal cord injury Infections, particularly pneumonia, are the primary cause of mortality in individuals with spinal cord injury (SCI).1 Several factors may contribute to the high rate of infections in the SCI population, including motor paralysis and reduced reflexes resulting in aspiration, invasive procedures, and so-called SCIinduced immune depression syndrome (SCI-IDS). 2,3SCI-IDS is thought to occur when the conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Addressing dysphagia may decrease the risk of aspiration pneumonia, which may lead to improved long-term outcomes (ie, functional independence and life expectancy). 18 Additionally, Logemann mentioned that tracheostomy and/or ventilator dependence makes BSE difficult and therefore subsequent VFSS is required; however, no literature or data were referenced to support this assertion. 10 We found that BSE can be performed accurately at the bedside to screen for dysphagia regardless of invasive mechanical ventilator dependence or tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing dysphagia may decrease the risk of aspiration pneumonia, which may lead to improved long-term outcomes (ie, functional independence and life expectancy). 18 Additionally, Logemann mentioned that tracheostomy and/or ventilator dependence makes BSE difficult and therefore subsequent VFSS is required; however, no literature or data were referenced to support this assertion. 10 We found that BSE can be performed accurately at the bedside to screen for dysphagia regardless of invasive mechanical ventilator dependence or tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the stratified models, the imputed and complete case analyses produced differing results in AIS B and C subgroups. 2 To address the question whether inaccuracy in the imputations may be a reason for such disparities rather than nonrandom dropout, 3 we compare the sociodemographic and neurologic baseline of complete cases with cases lost to FIM motor examinations at 1 or 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…The study included patients enrolled between 1995 and 2005 and the incidence of infections as well as the management of care after SCI may have changed throughout this time frame. 3 To reveal temporal differences in the rate of Pn/Wi and evaluate their potential to influence the FIM motor analysis, we compare the Pn/Wi rate by periods of enrollment (1995-1999 vs 2000-2005) and include the enrollment period as an explanatory variable in the linear models.…”
Section: Methodsmentioning
confidence: 99%